Development of Acid-Hydrolysed and Enzyme-Hydrolysed Winged Bean and Soybean Proteins - Choo, Wee Sim (2004)
Hydrolysed vegetable protein (HVP) is a savoury flavouring material obtained by acid, alkaline or enzymatic hydrolysis of a proteinaceous substrate. Traditionally, hydrolysis is often carried out using hydrochloric acid. However, the presence of 3-monochloropropane-1,2-diol (3-MCPD), a chemical contaminant in acid-hydrolysed vegetable protein pose a potential health risk to its users. Enzymatically hydrolysed vegetable protein, produced using proteolytic enzymes is a newer alternative to the traditional HVP. Common source of raw material in the industry for producing HVP is soybean. Winged bean (Psophocarpus tetragonolobus (L.) DC.) known locally as “kacang botor” is a tropical plant that contains high protein content, and virtually duplicate soybeans in composition and nutritional value. Based on Response Surface Methodology (RSM), the optimum conditions for producing acid-hydrolysed winged bean (aHWBP) and soybean (aHSBP) proteins were 7 hours and 5 hours of hydrolysis with hydrochloric acid at 125C, respectively. Proteolytic hydrolysis using 2.1% Flavourzyme 500L in aqueous 29% winged bean slurry (8% protein) for 11 hours, and proteolytic hydrolysis using 2.4% Flavourzyme in aqueous 26% soybean slurry (8% protein) for 16 hours were selected as the optimum conditions for producing enzyme-hydrolysed winged bean (eHWBP) and soybean (eHSBP) proteins, respectively. The proteolysis was preceded by treatment with 2% Viscozyme L in aqueous 29% winged bean or 26% soybean slurry. Alkaline thermal treatment using sodium hydroxide at pH 8.5 for 2 hours at 100C effectively reduced the 3-MCPD contents of aHWBP and aHSBP to undetectable levels. It did not cause major changes to other chemical and sensory properties of the HVP. Significant reduction in bitterness of eHWBP and eHSBP without changes to their chemical and sensory properties were obtained after treatment of the hydrolysates with 0.1% (w/w) -cyclodextrin. Enzymatic hydrolysis led to the production of 3-MCPD as well but the level was very low and within the permissible level. aHWBP and aHSBP were dark brown in colour with strong savoury flavours whereas eHWBP and eHSBP were lighter in colour and had a much less pronounced savoury flavour. Both aHWBP and eHWBP have their own distinct flavours which are different from that of soybean-derived flavours. aHWBP and aHSBP can be used as both taste-donor and taste-enhancer flavouring materials whereas eHWBP and eHSBP can be used as a base note flavouring material. Winged bean seeds can indeed be a new source of raw material for producing HVP.